COVID-19 and pregnancy: the fruitful experience of the university hospital of Tangier Morocco with hydroxychloroquine and anti-retroviral treatment - Aouali, Karima; Moustaid, Houda; Moustaid, Houda; Benkirane, Saad; Benkirane, Saad (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
The coronavirus disease 2019 (COVID-19) caused by the emerging virus, severe acute respiratory distress syndrome coronavirus 2 (SARS-CoV-2), was announced as a pandemic by the World Health Organization as a global public health emergency. Since the first case of COVID-19 was declared the Moroccan government set up drastic preventative measures to deal with the spread of the virus such as compulsory containment, telework, distance education, use of masks in public places, and many other preventive measures. Pregnant women require special attention in relation to prevention, diagnosis and management. We herein reported a prospective observational study that aims to evaluate the security and effectiveness of hydroxychloroquine on pregnant women with corona virus disease. Our study is a prospective study performed in the three hospitals specialized on corona virus disease 2019 in tangier morocco. We included pregnant women hospitalized with COVID-19 and reproductive-aged. Most cases took the hydroxychloroquine treatment. The maternal outcomes under hydroxychloroquine appear good in most cases for both mother and child and seemed to be safe according to several studies on its use for rheumatic diseases. In the absence of more robust data, this treatment might be best practice in countries that can’t afford the expensive antiviral treatment in this outbreak especially in emergency situations. <!–EndFragment–>